2019
DOI: 10.19184/korlantas-jirs.v2i1.15028
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Perilaku Pengendara Terhadap Kecelakaan Pejalan Kaki-Sepeda Motor

Abstract: Accidents within rider and pedestrian are increased during the last five years period. Conflict street users occur due to factors such as behavior and facility available. This research aims to analyze rider behavior and its influence on the pedestrian-motorcycle accident.  The research location is North Sulawesi Province, with the distribution of the questionnaire. Accident data reference is used to evaluate factors that influence the accident. Research result shows differences and similarity judgment for ride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…On the other side, this research also found that using the sidewalk while riding is more dangerous, with the estimated risk about 0.371 times higher to likely causing the motorcycle accidents to riders and pedestrians compared to students who did not use the sidewalk when riding the motorcycle. This is in line with research conducted by (Makalew et al, 2019) in 2019 in North Sulawesi, which stated that there was a significant correlation with traffic accidents that happened towards the society who lives in rural and urban areas where it was stated that it was 32.5 times higher to likely causing the accidents. From this fact, communities, especially students, need to be aware that the function of the sidewalk is clearly for pedestrians.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the other side, this research also found that using the sidewalk while riding is more dangerous, with the estimated risk about 0.371 times higher to likely causing the motorcycle accidents to riders and pedestrians compared to students who did not use the sidewalk when riding the motorcycle. This is in line with research conducted by (Makalew et al, 2019) in 2019 in North Sulawesi, which stated that there was a significant correlation with traffic accidents that happened towards the society who lives in rural and urban areas where it was stated that it was 32.5 times higher to likely causing the accidents. From this fact, communities, especially students, need to be aware that the function of the sidewalk is clearly for pedestrians.…”
Section: Discussionsupporting
confidence: 89%
“…However, there are still many motorcycle riders who still pass through the sidewalk. From this kind of condition, it can be assumed that some of the riders do not put pedestrian safety into considerations, and this could worsen the social impact in which such attitudes of riders could trigger the potential of the accident to become higher (Makalew et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Faktor utama terjadinya kecelakaan di jalan adalah kesalahan pengemudi dengan persentase sebesar 66,89%. Dalam faktor manusia, kurangnya antisipasi terhadap kondisi jalan dan lingkungan menjadi penyebab utama kecelakaan sebanyak 1.688 kasus, diikuti oleh keadaan mengantuk sebanyak 1.568 kasus [4]. Hal ini didukung dengan data pada tahun 2020 yang menyatakan terjadinya penurunan arus lalu lintas kendaraan akibat adanya pembatasan sosial.…”
unclassified